The Role of Social Capital and Social Innovation in Economic Growth - Bathuure, Isaac Akpemah (The Economics and Finance Letters, 2021)
The study assessed the role of social capital and social innovation in economic growth. Nonetheless, a panel of 147 countries was sampled from 2009 to 2017, and econometric panel techniques were utilized to arrive at a statistical conclusion. The techniques used in the estimation are contemporaneous correlation estimators; thus, panel corrected standard errors, panel generalized least square with correlation disturbances, and generalized linear model. Upon estimations, the study concluded that social capital and social innovation strongly play a positive role in economic growth. Therefore, in pursuit of sustainable economic growth, social capital accumulation; thus, social trust and social networking are essential. Moreover, social innovations that are internet-related positively contribute to economic growth sustainably. The study recommends that investment in digital communication technologies should be prioritized because it improves material living standards because it lowers the cost of maintaining and creating professional and personal ties, strengthening the diffusion of knowledge and ideas, and further creating productivity spill overs positively. Also, policymakers should enact policies that offer triple triumph; thus, triumph for government, society, and individuals characterised by affordability, benefits, and add value to citizens' standard of living.